‘Cell knife’ for cancer: the clinician’s perspective - Zhou, Zihan; Chen, Yunhao; Wang, Yao; Hong, Yafang; Guan, Hongdan; Huang, Fenghao; Fu, Fenfang; Li, Xiaobo; Zheng, Rong; Xu, Benhua (Frontiers in Immunology, 2025)
Boron Neutron Capture Therapy (BNCT), often referred to as the ‘cell knife,’ represents a binary, tumor-selective therapeutic modality that minimizes damage to surrounding healthy tissues. This review provides a comprehensive clinical perspective on BNCT, addressing the radiobiological mechanisms and summarizing related clinical trials, with a particular emphasis on glioma and head and neck cancers. Furthermore, the paper touches upon the synergistic potential of BNCT when integrated with other treatment modalities, such as proton and carbon ion radiotherapy, alternative neutron capture therapies, ultrasound, and immunotherapy. These combined approaches may offer promising avenues for future research, potentially enhancing the therapeutic index and expanding the applicability of BNCT in oncological practice.